Feasibility of couple-based expanded carrier screening offered by general practitioners - Schuurmans, Juliette (Eur J Hum Genet, 2019)
Expanded carrier screening (ECS) aims to inform couples’ reproductive choice, preferably before conception. As part of an implementation study in which trained general practitioners (GPs) offered a population-based ECS couple-test, we evaluated the feasibility of the test-offer and degree of participant informed choice (IC). Trained GPs from nine practices in the northern Netherlands invited 4295 female patients aged 18–40 to take part in couple-based ECS. Inclusion criteria were having a male partner, planning for children and not being pregnant. We evaluated the feasibility of the organizational aspects, GP competence and the content of the pre-test counselling. Participant satisfaction, evaluation of pre-test counselling and degree of IC were measured using a longitudinal survey. We explored GP experiences and their views on future implementation through semi-structured interviews. 130 consultations took place. All participating GPs were assessed by genetic professionals to be competent to conduct pre-test counselling. Most (63/108 (58%)) consultations took place within the planned 20 min (median 20, IQR 18–28). GPs considered couples’ prior knowledge level an important determinant of consultation length. 91% of patients were (very) satisfied with the GP counselling. After pre-test counselling, 231/237(97%) participants had sufficient knowledge and 206/231(88%) had a positive attitude and proceeded with testing. Our pilot demonstrates that offering couple-based ECS through trained and motivated GPs is feasible. Future large-scale implementation requires a well-informed general public and a discussion about appropriate reimbursement for GPs and health care coverage for couples. Providing (more) test information pre-appointment may help reduce average consultation time.